If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(3m + 4) + -7m = -4 Reorder the terms: 9(4 + 3m) + -7m = -4 (4 * 9 + 3m * 9) + -7m = -4 (36 + 27m) + -7m = -4 Combine like terms: 27m + -7m = 20m 36 + 20m = -4 Solving 36 + 20m = -4 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 20m = -4 + -36 Combine like terms: 36 + -36 = 0 0 + 20m = -4 + -36 20m = -4 + -36 Combine like terms: -4 + -36 = -40 20m = -40 Divide each side by '20'. m = -2 Simplifying m = -2
| 200(0)-15=y | | 15q-3[4q-6]=3q+9-9q | | 5x+4=26+46 | | 0.3(3x+0.5)= | | -2(5x+2)=-3x+7 | | 12=6ax-4xb | | -25-(-15)= | | 3+y4=-y8 | | 10(12)=5(18) | | 47-6x=19+8x | | 7Z-3y=2 | | 6ax-4xb=12 | | N+(4.361)=59.78 | | -41=-3x-5 | | y=5.00+0.25x | | 9(x-1)+x=11 | | 6-9x=6x-9x-6 | | (x^2)+2x+40=(x^2)-x+190 | | 36r^2-1=0 | | 9y-8-6y+7=0 | | -25+55.5+(-29)= | | 6(-3x-3)=5x | | 7x+5x-54=72-6x | | 2c-58=7c-24 | | -15=5b+12-2b+b | | 3x+2+2x-1=6x-20 | | 35.8x+5.90=220.7 | | 17=6z-1 | | 36+(4x-9)=c(2x+1)+25 | | .666=3r | | 18x^2+18y^2-12x+9y+7=0 | | x^2-15x-15=-6x-5 |